Pertumbuhan Ekonomi dan Pengangguran Terhadap Tingkat Kemiskinan di Jayapura Pada Tahun 2017-2022 - Rahmianti, Siti; Siompo, Nirfa; Yeubun, Shimah Fauziah; Affandy, Fachrudin Fiqri (Jurnal Pendidikan Ekonomi Undiksha, 2024)
In various developing countries, such as Indonesia, they still face problems related to economic growth or unemployment. This research aims to understand the effect of population growth on economic growth and unemployment rates in Jayapura City. In this research, the dependent variable is the open unemployment rate, the independent variable is population growth, and the intervening variable is economic growth. The data analysis used in this research is population growth versus economic growth. This research uses secondary data from Jayapura City for 5 years as measured by BPS, namely from 2017-2022, using a qualitative approach. These results show that economic growth influences the level of poverty, and increasing economic growth can reduce the level of poverty, as well as unemployment, which can influence the level of poverty, with high levels of unemployment affecting economic growth and unemployment simultaneously. The results of the study show that economic growth, partially or individually, has a significant effect on poverty levels. In addition, partial or individual unemployment has no effect on poverty levels. However, economic growth and unemployment simultaneously or together affect poverty levels.